A multi-indicator approach for identifying shoreline sewage pollution hotspots adjacent to coral reefs. Issue 1 (April 2018) - Abaya, Leilani M.; Wiegner, Tracy N.; Colbert, Steven L.; Beets, James P.; Carlson, Kaile'a M.; Kramer, K. Lindsey; Most, Rebecca; Couch, Courtney S.
Abstract: Sewage pollution is contributing to the global decline of coral reefs. Identifying locations where it is entering waters near reefs is therefore a management priority. Our study documented shoreline sewage pollution hotspots in a coastal community with a fringing coral reef (Puakō, Hawai'i) using dye tracer studies, sewage indicator measurements, and a pollution scoring tool. Sewage reached shoreline waters within 9 h to 3 d. Fecal indicator bacteria concentrations were high and variable, and δ 15 N macroalgal values were indicative of sewage at many stations. Shoreline nutrient concentrations were two times higher than those in upland groundwater. Pollution hotspots were identified with a scoring tool using three sewage indicators. It confirmed known locations of sewage pollution from dye tracer studies. Our study highlights the need for a multi-indicator approach and scoring tool to identify sewage pollution hotspots. This approach will be useful for other coastal communities grappling with sewage pollution. Highlights: Sewage reached shoreline waters within 9 h to 3 d. Shoreline FIB concentrations were high and variable. Shoreline δ 15 N macroalgal values were indicative of sewage. Shoreline nutrients were two times higher than those in upland groundwater. Pollution score successfully confirmed known locations of sewage pollution.